Bioconversion of Napier Grass Mixed with Soybean Curd Residue Producing Bioethanol through Simultaneous Saccharification and Fermentation in a Solid State Culture - T Taufikurahman; Jessica Jessica (3BIO: Journal of Biological Science, Technology and Management, 2020)
Napier grass is a promising lignocellulosic biomass for bioethanol production because of its high cellulose content and high annual productivity. Converting a lignocellulosic biomass into a bioethanol usually takes two steps which resulted in a long processing time and sometimes includes the utilization of hazardous chemicals. Simultaneous saccharification and fermentation in a solid-state culture using single bioconversion agent, Neurospora sitophila Shear, can reduce the overall processing time and also increase the yield of the products. The research is aimed to determine the optimum aerobic and micro-aerobic conditions that yields the highest enzyme activity and bioethanol concentration from the mixture of Napier grass and soybean curd residue. The saccharification and fermentation process was conducted in the laboratory using an incubator at 33oC. The cellulase enzyme activity was calculated as FPAse. The highest activity achieved was 0.538 filter paper unit with the optimum mass ratio of Napier grass to soybean curd residue was 1:1 on the second day of cultivation period. The fermentation process was conducted aerobically for two days and then followed by six days of micro-aerobic fermentation, resulting in the highest bioethanol yield of 2.12% (w/w) at the end of the culture period. The optimum mass ratio was found to be 9:1. This study shows that Napier grass and simultaneous saccharification and fermentation method has a great potential for cellulase and bioethanol production, but further improvement on the micro-aerobic system is needed to maximize the bioethanol yield.